Co-Application of 24-Epibrassinolide and Titanium Oxide Nanoparticles Promotes Pleioblastus pygmaeus Plant Tolerance to Cu and Cd Toxicity by Increasing Antioxidant Activity and Photosynthetic Capacity and Reducing Heavy Metal Accumulation and Translocation - Abolghassem Emamverdian; Yulong Ding; James Barker; Guohua Liu; Mirza Hasanuzzaman; Yang Li; Muthusamy Ramakrishnan; Farzad Mokhberdoran (MDPI AG, 2022)
The integrated application of nanoparticles and phytohormones was explored in this study as a potentially eco-friendly remediation strategy to mitigate heavy metal toxicity in a bamboo species (Pleioblastus pygmaeus) by utilizing titanium oxide nanoparticles (TiO2-NPs) and 24-epibrassinolide (EBL). Hence, an in vitro experiment was performed to evaluate the role of 100 µM TiO2 NPs and 10−8 M 24-epibrassinolide individually and in combination under 100 µM Cu and Cd in a completely randomized design using four replicates. Whereas 100 µM of Cu and Cd reduced antioxidant activity, photosynthetic capacity, plant tolerance, and ultimately plant growth, the co-application of 100 µM TiO2 NPs and 10−8 M EBL+ heavy metals (Cu and Cd) resulted in a significant increase in plant antioxidant activity (85%), nonenzymatic antioxidant activities (47%), photosynthetic pigments (43%), fluorescence parameters (68%), plant growth (39%), and plant tolerance (41%) and a significant reduction in the contents of malondialdehyde (45%), hydrogen peroxide (36%), superoxide radical (62%), and soluble protein (28%), as well as the percentage of electrolyte leakage (49%), relative to the control. Moreover, heavy metal accumulation and translocation were reduced by TiO2 NPs and EBL individually and in combination, which could improve bamboo plant tolerance.